Դանիել Վարուժան. ազատության առաքյալը - Հակոբյան, Լեռնիկ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Исполнилось 140 лет со дня рождения одного из выдающихся представителей западноармянской литературы –Даниэла ВаружанаД. Варужан родился 20 апреля 1884 г. в Западной Армении, в селе Бргник Себастии. Учился в сельской школе, затем в Константинополе, Венеции, а также в университете города Гента в Бельгии. Получив образование, занимался педагогической деятельностью. Даниэл Варужан – один из столпов новой армянской литературы, неутомимый певец и идеолог национально-освободительной борьбы. Стержнем его поэтических сборников «Содрогания» (1906), «Сердце нации» (1909), «Языческие песни» (1912) и «Песня хлеба» (1921) является Армения и армянский народ. Путем отмщения, национально-освободительной борьбы, всенародного восстания достичь свободы и независимости – вот идеологическая основа сборников. В центре поэтических акцентов Варужана находится также прославление мирной жизни, труда, природы, общечеловеческих ценностей. 24 апреля 1915 г. Д. Варужан был арестован турецкими властями и сослан в Чанкыры. 26 августа, по дороге в Айаш, был зверски убит. 140 years have passed since the birth of Daniel Varoujan – one of the most eminent representatives of the Western Armenian literature. D. Varoujan was born on April 20, 1884, in the village of Prgnik, Sebastia vilayet. First, he studied at a village school, then in Constantinople, Venice and at Ghent University in Belgium. After receiving his education, he was engaged in teaching activities. Daniel Varoujan is one of the pillars of the new Armenian literature, tireless singer and ideologue of the national liberation struggle. The core of his poetry collections “Shivers” (1906), “The Heart of the Race” (1909), “Pagan Songs” (1912) and “The Song of the Bread” (1921) is Armenia and Armenian people. Тhe ideological basis of the collections is the achievement of freedom and independence by means of revenge, national liberation struggle and national uprising. Glorification of peaceful life, labour, nature and universal human values are also at the center of Varujan’s poetic accents. On April 24, 1915, Daniel Varoujan was arrested by Turkish authorities and exiled to Chankiri. On August 26, on the way to Ayash, he was brutally murdered.
Keywords: Հայ գրականագիտություն; Հայ գրողներ